2010
DOI: 10.1128/jb.01445-09
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Pseudomonas syringae Identifies New Genes, Noncoding RNAs, and Antisense Activity

Abstract: To fully understand how bacteria respond to their environment, it is essential to assess genome-wide transcriptional activity. New high-throughput sequencing technologies make it possible to query the transcriptome of an organism in an efficient unbiased manner. We applied a strand-specific method to sequence bacterial transcripts using Illumina's high-throughput sequencing technology. The resulting sequences were used to construct genome-wide transcriptional profiles. Novel bioinformatics analyses were develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
132
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(137 citation statements)
references
References 88 publications
(84 reference statements)
5
132
0
Order By: Relevance
“…Second, in our profiles we experienced fluctuating sequence read coverage, and at times the read profiles were fragmented by gaps without read coverage even within regions with high read counts. Other RNAseq-based transcriptome studies have also reported fluctuating read coverage (15,23,59), which may be caused by stochastic artifacts introduced during sample preparation or be due to possible degradation of RNA (85). During the cDNA library preparation, sequencing biases may be introduced due to different efficiencies in fragmentation, reverse transcription, and amplification, all of which can be affected by sequence composition as well as the level of transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…Second, in our profiles we experienced fluctuating sequence read coverage, and at times the read profiles were fragmented by gaps without read coverage even within regions with high read counts. Other RNAseq-based transcriptome studies have also reported fluctuating read coverage (15,23,59), which may be caused by stochastic artifacts introduced during sample preparation or be due to possible degradation of RNA (85). During the cDNA library preparation, sequencing biases may be introduced due to different efficiencies in fragmentation, reverse transcription, and amplification, all of which can be affected by sequence composition as well as the level of transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription start point (+) for each transcriptional group in the dar gene cluster was determined using the 59 rapid amplification of cDNA ends (RACE) method (Carrió n et al, 2012;Filiatrault et al, 2010;Maruyama et al, 1995). The synthesis of single-stranded cDNA was performed using total DNA-free RNA obtained from a P. chlororaphis PCL1606 culture growing in TPG medium for 24 h at 25 uC as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…In the past 10 years, the development of new approaches based on high-resolution tiling arrays and RNA deep sequencing (RNA-seq) has uncovered that a significant proportion (depending on the study, varying between 3% and >50%) of protein coding genes are also transcribed from the reverse complementary strand (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). In most cases, overlapping transcription generates a noncoding antisense transcript whose size can vary between various tens of nucleotides (cisencoded small RNAs) to thousands of nucleotides (antisense RNAs).…”
mentioning
confidence: 99%